In-contest body acceleration profiles for the judo male and female weight divisions - Santos, Luis; Federolf, Peter A.; Schneider, Friedemann; Pocecco, Elena; Fernández-Río, Javier; Iglesias-Soler, Eliseo; Carballeira-Fernández, Eduardo; Uriarte, Sugoi; Dopico-Calvo, Xurxo (Frontiers in Sports and Active Living, 2024)
Introduction This study aimed to determine the body accelerations (BA) profile of the judo contest of the male and female weight divisions and to ascertain the involvement of the vertical, mediolateral and anteroposterior axes in it. Methods Forty-eight male and forty-eight female national and international level athletes (some of them medalists in World, European and national championships) participated in a 5-min simulated contest (official fight time plus breaks) against an opponent of the same sex and weight division, wearing an accelerometer. Heart rate, blood lactate and ratings of perceived exertion were recorded to certify that the athletes performed the fullest. Results The t2way test expressed differences in the athletes' BA (p = 0.001) and three profiles were identified: the light/middle weight male divisions, the light/middle weight female divisions and the heavy male and female ones. Athletes of all weight divisions performed their BA during the contest in all three directions (the one-sample Person's chi-square did not detect any significantly predominant one: p = 0.400, p = 0.631, p = 0.844, p = 0.749, p = 0.644 and p = 0.895, for male light, moderate and heavy, female light, moderate and heavyweight athletes, respectively). Monte Carlo method simulations suggested as the most likely scenarios those with BA involving all axes, with a slight preference of the anteroposterior and mediolateral ones. Discussion These results suggest that the demands on judo athletes in a contest differ between weight classes and sexes.